THE FEATURES OF PHRASEOLOGICAL SYNONYMIC ROWS OF ENGLISH AND UZBEK LANGUAGES (Web of Teachers: Inderscience Research, 2024)
This article supplies us with the data about figurative, stylistic coloring of phraseological synonymic rows of English and Uzbek languages.